ALLERGY TO THE PRODUCTION DUST AT WORKERS OF INTEGRATED COTTON MILL (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Professional allergosis has great medical and social significance. Due to allergy millions of working days are got lost, the patients had received disablement, and compeled them to change their profession.